A Polyanionic Tartrate‐containing Temperature‐responsive Hydrogel. Issue 21 (27th September 2022) - Loh, Wei Wei; Huang, Miao; Goh, Leonard; Lim, Chen Chuan; Goh, Rubayn; Lin, Qianyu; Guo, Liangfeng; Loh, Xian Jun; Lim, Jason Y. C.
Abstract: Thermogels, a class of hydrogels which show spontaneous sol‐gel phase transition when warmed, are an important class of soft biomaterials. To date, however, most amphiphilic polymers that are able to form thermogels in aqueous solution are uncharged, and the influence of ionisable groups on thermogelation are largely unknown. Herein, we report the first example of a polyanionic amphiphilic multi‐block copolymer, containing multiple pendant carboxylate groups, that can form transparent thermogels spontaneously when warmed up to physiological temperature. We demonstrate that introducing negative charges onto thermogelling polymers could significantly alter the properties of the micelles and thermogels formed. Furthermore, the polymer's polyanionic character provides new options for modulating the gel rheological properties, such as stiffness and gelation temperatures, through electrostatic interactions with different cations. We also demonstrated that the polyanionic thermogel allowed slower sustained release of a cationic model drug compound compared to an anionic one over 2 weeks. The findings from our study demonstrate exciting new possibilities for advanced biomedical applications using charged polyelectrolyte thermogel materials. Abstract : The first fully‐synthetic polyanionic thermogelling polymer is reported herein which is able to exhibit sol‐gel transitions when warmed to physiological temperature. By virtue of the polymer's pendant anionic carboxylate groups, the thermogel's rheological properties can be modulated by different metal cations and can release cationic model drugs more slowly than anionic ones.